2023
DOI: 10.12998/wjcc.v11.i5.1144
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of granulomatosis with polyangiitis using tocilizumab combined with glucocorticoids: A case report

Abstract: BACKGROUND Tocilizumab is a humanized monoclonal antibody against the interleukin-6 (IL-6) receptor that is commonly used to treat large vessel vasculitis and antineutrophil cytoplasmic antibody-related small vessel vasculitis. However, tocilizumab in combination with glucocorticoids for successfully treating granulomatosis with polyangiitis (GPA) has rarely been reported. CASE SUMMARY Here, we report a 40-year-old male patient who suffered GPA for 4 years. He was treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Tocilizumab, an anti-IL-6R antibody, has shown good clinical benefits in the biological treatment of patients with giant cell arteritis ( Antonio et al, 2022 ). Tang et al (2023) reported findings from a patient with refractory GPA and elevated IL-6 expression. After treatment with tocilizumab, the patient’s symptoms improved and the levels of inflammatory markers, including IL-6, normalized.…”
Section: Biologicsmentioning
confidence: 99%
“…Tocilizumab, an anti-IL-6R antibody, has shown good clinical benefits in the biological treatment of patients with giant cell arteritis ( Antonio et al, 2022 ). Tang et al (2023) reported findings from a patient with refractory GPA and elevated IL-6 expression. After treatment with tocilizumab, the patient’s symptoms improved and the levels of inflammatory markers, including IL-6, normalized.…”
Section: Biologicsmentioning
confidence: 99%